Significance of Pretreatment Neutrophil-to-Lymphocyte Ratio in Mucoepidermoid Carcinoma of Pediatrics: A Multicenter Study - Gao, Hua; Gao, Qing; Sun, Jinlan (Frontiers in Pediatrics, 2020)
Background: Our goal was to analyze the value of the pretreatment neutrophil-to-lymphocyte ratio (NLR) in the prognosis of pediatrics with parotid mucoepidermoid carcinoma (MEC). Methods: Patients (≤18 years old) undergoing surgical treatment for primary parotid MEC were enrolled from multiple clinical centers retrospectively. The Chi-square test was used to analyze the associations between clinicopathological variables and the NLR, the main study endpoints were recurrence-free survival (RFS) and disease-specific survival (DSS), the prognostic value of NLR was assessed by Kaplan-Meier method and and Cox model analysis. Results: There were 88 patients included in total with mean NLR of 2.32 (range: 1.8-6.0). Histologic tumor grade and tumor stage were associated with the NLR significantly. The 10-year RFS rates were 98% and 81% for patients with an NLR <2.32 and patients with an NLR ≥2.32, respectively, the difference was significant (p=0.010). The 10-year DSS rate was 97% and 81% for patients with an NLR <2.32 and patients with an NLR ≥2.32, respectively, the difference was not significant (p=0.072). The independence of NLR in predicting the RFS was furtherly confirmed in Cox model analysis Conclusion: The NLR significantly affects the prognosis in pediatrics with primary parotid MEC.